1H-NMR-based metabolomic profiles of different sweet melon (Cucumis melo L.) Salento varieties: Analysis and comparison. (December 2018) - Girelli, Chiara Roberta; Accogli, Rita; Del Coco, Laura; Angilè, Federica; De Bellis, Luigi; Fanizzi, Francesco Paolo
Abstract: Melon ( Cucumis melo L .) is a significant source of substances able to provide human health benefits. From the 18th century in the Salento area (Apulia region), the cultivation of melon varieties ( C. melo L. ) has always been intense. Over the years, the production of this fruit has involved a large number of selected and preserved varieties in the different local districts. Unfortunately, most of the characteristics of locally grown vegetable varieties do not match the food industry requirements. Moreover, the agricultural land abandon leads these varieties to quickly disappear, thus affecting the intraspecific biodiversity. In order to characterize the inter-variety diversity of sweet melon ( C. melo L . ssp. melo group inodorus ) and the potential differences in the nutritional quality of fruits, a first investigation on the juice of five sweet melon varieties (locally known as "allungato", "scurzune", "egiziano", "minna de monaca", "pinto"), cultivated exclusively in the Salento area, was performed by 1 H-NMR spectroscopy and Multivariate Analysis (MVA). The analysis grouped the samples into clusters according to the different variety. Interestingly, a different sugar (mono and disaccharides) content was observed among the grouped varieties, being sweetness the main characteristic of sweet melon quality and taste. A relative higher accumulation of monosaccharides (α-d and β-d glucose and α/β-d fructose) was found, in particular for the "minna de monaca" with respect to "allungato", "egiziano" and "pinto" varieties. Moreover, a marked high content of polyphenols and aromatic aminoacids as phenylalanine and tyrosine characterize the "allungato", "minna de monaca" and "pinto" varieties. An NMR-based metabolomic approach was used for the first time to describe these local landraces. This method may integrate other actions in order to achieving a reduction in the current rate of erosion of the biodiversity of Apulian horticultural species. Graphical abstract: Highlights: 1 H NMR based MVA comparison of local sweet melon varieties metabolic profiles was perfomed. "Allungato", "minna de monaca" and "pinto" varieties showed good nutrition properties. Assessing nutrition properties by metabolic profiling could promote local landraces demand. This method could integrate actions to reduce the current erosion rate of Apulian biodiversity.